2014
DOI: 10.1186/1477-7517-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smokeless tobacco packaging on perceptions and beliefs among youth, young adults, and adults in the U.S: findings from an internet-based cross-sectional survey

Abstract: BackgroundResearch demonstrates that tobacco packaging elements (including health warning labels, descriptive characteristics, and corporate branding) are associated with knowledge of health risks and product appeal with cigarettes. Yet, little research has assessed this with smokeless tobacco (SLT) packaging. This study evaluates the association between three SLT packaging elements with knowledge of health risks and perceptions of novelty and appeal. Additionally, we assess how effects of these messages may d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 30 publications
1
38
1
1
Order By: Relevance
“…To the best of our knowledge, only two published studies32 33 have experimentally tested attributes of smokeless tobacco health warnings: one in the USA and one in Canada. The US study32 examined design elements such as flavour descriptors and corporate branding, in addition to pictorial versus text health warnings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only two published studies32 33 have experimentally tested attributes of smokeless tobacco health warnings: one in the USA and one in Canada. The US study32 examined design elements such as flavour descriptors and corporate branding, in addition to pictorial versus text health warnings.…”
Section: Introductionmentioning
confidence: 99%
“…The US study32 examined design elements such as flavour descriptors and corporate branding, in addition to pictorial versus text health warnings. The findings demonstrated that pictorial warnings made respondents more likely to consider the health risks of smokeless tobacco use (vs text-only warnings).…”
Section: Introductionmentioning
confidence: 99%
“…Based on some research findings it has been found that the graphic and text warnings on SLT products are robustly associated with the perception of health risk and appeal of the product [20,21]. This goes on to prove our point that repeated awareness about the ill effects of tobacco consumption in any form, be it psycho-education; psychotherapeutics, branding or legislation has a positive co-relation with reducing tobacco intake.…”
Section: Discussionmentioning
confidence: 93%
“…33 Youth shown tobacco packages with or without a flavor descriptor (primarily snus and dissolvable tobacco) were more likely than older adults to associate the flavor descriptor with better taste, more appeal, and reduced health risks. 34 …”
Section: Discussionmentioning
confidence: 99%